KEBIJAKAN PERENCANAAN DAN PEMBANGUNAN DESA EKOWISATA DAN PARIWISATA DI INDONESIA - Padriadi Wiharjokusumo (Jurnal Ilmiah Akomodasi Agung, 2020)
The development of a tourism or ecotourism village requires careful integrated planning. The village shows its role and function as a source of inspiration for environmental and cultural preservation. However, it is not easy to do. Developing a tourist village is an extraordinary job, multi-sectoral and requires collaboration. Ecotourism planning requires integration of the macro, ecosystem and local levels. Planning at the macro level provides the basis for legal management at the ecosystem and local levels. Ecosystem-level planning establishes an environmental and cultural vision and coordinates regional management of a destination. Planning at the local level develops quality management services, participation and empowerment of local communities. The development of ecotourism services in villages includes efforts (i) developing local empowerment, (ii) developing infrastructure to meet environmental preservation, (iii) developing governance to gain positive experiences and welfare, (iv) integrating tourism promotion through product development and market segmentation , and (v) interpretation and education to offer education on cultural and environmental preservation.